Climate change a necessity in the process of improvement and cultivation of the grapevine - E. Alexandrov (Romanian Journal of Horticulture)
Climate change manifests itself not only in high temperatures, but also a distribution of rainfall during a vegetative year, extreme weather events (waves of heat, heavy rains, hail, frost, and strong winds) and prolonged drought, which must be taken into account in the complex, in the process of plant growth and development. Climate change solutions can be not only profitable, but can affect the level and quality of life of the population while protecting the environment. To improve the current situation, it is necessary to take actions that contribute to reducing emissions, a adapting to the consequences of climate change, and financing the necessary adaptation measures. Evaluating the climatic conditions of the Republic of Moldova, we find that in the past the climate was of a temperatecontinental type, as a result of the evaluation of these conditions over the years, a trend of change was found, towards the creation of arid conditions. Climate change requires the creation of genotypes with increased adaptability and the revision of agricultural plant cultivation technologies. Climate change requires the creation of genotypes with increased adaptability and the revision of agricultural plant cultivation technologies.